Management of an Infected Nonunion of an Opening-Wedge High Tibial Osteotomy with 2-Stage Implantation of Rotating Hinge Knee Prosthesis - Sandrine Mariaux; Olivier Borens (Case Reports in Orthopedics)
Introduction. High tibial osteotomy (HTO) is a frequent and effective treatment for unicompartmental gonarthritis. Only a few articles are focused on the treatment of infected nonunion. Patient and Method. A 50-year-old obese patient was operated on by medial opening-wedge HTO. She developed a painful nonunion treated by hardware removal, allograft, and plate fixation. However, the nonunion persisted. 2 years later, cellulitis appeared with an abscess adjacent to the HTO plate. Despite surgical debridement and antibiotics, septic knee arthritis occurred. In a situation of infected nonunion and septic arthritis with chondrolysis, she was scheduled for a 2-stage total knee replacement (TKR). The infected tibial articular block was first resected and replaced by a cement spacer. After a short interval, the TKR was implanted. After 2 years, the patient walked pain-free with good knee function. Discussion. In the literature, different efficient treatments exist for infected nonunion after HTO, but comprehensive studies are missing for a consensus treatment. Current data are mostly based on case reports, since this pathology is quite rare. Conclusion. In a difficult situation of infected nonunion with septic knee arthritis, we performed a 2-stage knee prosthesis implantation. This led to an early mobilization and fast recovery.